The Web-Based Sales Information System for A Store in Tegal District - Yonathan Aditya Wijaya; Ridwan Sanjaya; T. Brenda Ch Ch (Soegijapranata Catholic University, 2023)
The development of information systems in the age of digital reform is very rapid, as the development of science and technology changes with the age of time. In mankind's lives, information systems play a crucial role in the quality of resources, both human resources, and natural resources, and can increase productivity in both services and goods. The development of the web-based information system application in the regional planning system is conducted using waterfall development methods. With the original shop website online, the owners make more money because the COVID-19 pandemic has felt the income is rapidly falling. With the website of the original store online, the original store owner is happy and content to increase income before there was no website.